Photoelectrical Properties of aluminum Oxide After Implantation with Cobalt Ions; 10th International Conference on Modification of materials with Particle Beams and Plasma Flows, Tomsk, September 19-24, 2010 - Kabyshev A. V. Alexander Vasilievich (2010, 2010)
Title screen